Sea urchin granuloma - Rossetto, André Luiz; Mora, Jamesson de Macedo; Haddad Júnior, Vidal [UNESP] (Instituto de Medicina Tropical, 2006)
Os acidentes por animais aquáticos traumatizantes e venenosos podem provocar morbidez importante em humanos. Equinodermos marinhos incluem mais de 6000 espécies de estrelas-do-mar, ouriços-do-mar, bolachas-de-praia e pepinos-do-mar. Vários equinodermos têm sido responsabilizados por acidentes em humanos. Granulomas por ouriço-do-mar são lesões de caráter granulomatoso, crônicas, causada por acidentes com espículas de ouriço-do-mar. Os autores relatam um caso típico de granulomas por ouriço-do-mar ocorrido em um pescador e enfatizam as implicações terapêuticas aplicadas.

Injuries caused by venomous and poisonous aquatic animals may provoke important morbidity in humans. The phylum Echinoderma include more than 6000 species of starfish, sea urchins, sand dollars, and sea cucumbers some of which have been found responsible for injuries to humans. Initial injuries by sea urchins are associated with trauma and envenomation, but later effects can be observed. Sea urchin granuloma is a chronic granulomatous skin disease caused by frequent and successive penetration of sea urchin spines which have not been removed from wounds. The authors report a typical case of sea urchin granuloma in a fisherman and its therapeutic implications.
Granulomas por ouriços-do-mar
Keywords: Venomous aquatic animals; Traumatic aquatic animals; Echinoderms; Sea urchin; Sea urchin granuloma; Foreign body granulomas